Mulheres no poder: a constituição do ethos retórico em discursos de presidentas - Verzola, Marina Gláucia (2012)
During the period of government elections, we notice, in most communities, discussions about the main candidates, their lives, speeches, and expectations. Politics is part of all citizens’ daily life and, therefore, it becomes even more relevant when we analyze the world political situation and we find out that: even though this situation has been changing, women continue to occupy a very restricted place when it refers to leadership positions. In 2010, only eight percent of the world leaders were women, this means 18 female leaders, with the current president of Brazil, Dilma Rousseff. Regarding the reflections made about this situation, the aim of this work is to analyze how rhetorical ethos is constituted in the speeches of women presidents. To do this, it has been selected speeches from three women presidents who we believe are the most relevant ones, according to our aim: apart from our current Republic President, Dilma Rousseff, we chose two other contemporary government leaders, the president of Argentina, Cristina Fernández Kirchner and the President of Costa Rica, Laura Chinchilla Miranda. As theoretical basis, we made use of studies of Argumentation and Rhetoric about ethos, especially the works of Michel Meyer, Olivier Reboul and Chaïm Perelman and Lucie Olbrechts-Tyteca. In terms of methodology, once we have selected the corpus, we made the transcription of each one of the speeches. Then we analyzed the extracts that show the constitution of rhetorical ethos of the leaders selected for this work. Doing this, we could realize that the women presidents make use of very similar rhetorical strategies in order to constitute their ethos of good person. However, we also realize that each one of them gives attention to what is relevant in their society, what justify some differences in the construction of speeches.